Intimate partner homicide - Lysova, Alexandra (Routledge handbook of homicide studies, 2024)
Intimate partner homicide (IPH), also known as domestic or spousal homicide, is a serious and devastating form of violence within relationships. Women bear a disproportionate burden of IPH, with approximately one-third of all female homicides worldwide being committed by an intimate partner. This fact underscores the emphasis of IPH research on examining risk factors and developing preventive measures for male-perpetrated homicide of women. However, there are significant gaps in IPH research that require attention. First and foremost, it is crucial to recognize that IPH is not a singular phenomenon; rather, it encompasses various types of homicides within intimate partner relationships. This chapter presents a couple-based ecological typology of IPH, delineating three distinct types: couple conflict-related IPH, intimate terrorism IPH, and violent resistance IPH. This typology is framed within a broader ecological framework that incorporates individual and societal risk factors. A nuanced understanding of these distinctions can facilitate the development of tailored prevention strategies. Next, this chapter highlights the need to address gaps in knowledge concerning female-perpetrated IPH and IPH in same-sex couples. By expanding our understanding of these underrepresented aspects, we can gain more comprehensive insights into the dynamics of IPH and improve prevention efforts. The chapter concludes by examining the responses of the criminal justice system to IPH and the implications of the proposed couple-based ecological typology for enhancing preventive measures.